The effect of varying pressure on mechanical performance of pineapple leaf fiber reinforced poly lactic acid biocomposites - S.N.R, Ramli; S. H. S. M., Fadzullah; Z., Mustafa; M. R. M., Rejab; M. Z., Hassan (Centre for Advanced Research on Energy (CARe), 2017)
The biocomposites fabricated in this study is produced by reinforcing poly lactic acid with pineapple leaf fibers with length of 200 mm and 30 wt.% fiber loading. with consideration on using alkaline treatment for the fibers. The aim of this .sludy is to evaluate the effect of pressure applied during compression molding on the mechanical performance of the biocomposites. The unidirectional biocomposites plates with norminal thickness of 3mm were characterized in terms of their flexural and tensile properties in accordance to ASTM D790 and D3039 respectively. From die experimental results, it was found that thebiocomposites fabricated using a pressure of 1700 psi exhibit superior tensile and flexural properties in comparison to those fabricated using 200 psi pressure. Moreover, the alkaline treated pineapple leaf fibre reinferced biocomposites disclosed much higher flexural strength and modulus in cumparison to those of the untreated samples.